The Connection of Capital Leverage and Profitability by the Corporate Agriculture Enterprises - Herczeg, Adrienn (Acta Agraria Debreceniensis, 2009)
The analysis of capital system of agricultural corporations is a key issue of economics and the effect of it’s fluctuation can be observed on several fields of the life of corporations.It influences for example the assets-, financial- and income situation of the enterprises.The aim of this study is to analyse the connection between capital structure and profitability in order to reveal such a ratio for the capital leverage and liabilities, by which it can say, to that connect the profit or loss. By the analyse get activity- and size specified results.With the empyrical results I determine the quantile point between the profitable or the non profitable operating.